An adverse outcome pathway based in vitro characterization of novel flame retardants-induced hepatic steatosis - Negi, Chander K; Bajard, Lola; Kohoutek, Jiri; Blaha, Ludek (Environmental pollution (Barking, Essex, 2021)
A wide range of novel replacement flame retardants (nFRs) is consistently detected in increasing concentrations in the environment and human matrices. Evidence suggests that nFRs exposure may be associated with disruption of the endocrine system, which has been linked with the etiology of various metabolic disorders, including nonalcoholic fatty liver disease (NAFLD). NAFLD is a multifactorial disease characterized by the uncontrolled accumulation of fats (lipids) in the hepatocytes and involves multiple-hit pathogenesis, including exposure to occupational and environmental chemicals such as organophosphate flame retardants (OPFRs). In the present study we aimed to investigate the potential mechanisms of the nFRs-induced hepatic steatosis in the human liver cells. In this study, we employed an in vitro bioassay toolbox to assess the key events (KEs) in the proposed adverse outcome pathways (AOP) (s) for hepatic steatosis. We examined nine nFRs using AOP- based in vitro assays measuring KEs such as lipid accumulation, mitochondrial dysfunction, gene expression, and in silico approach to identify the putative molecular initiating events (MIEs). Our findings suggest that several tested OPFRs induced lipid accumulation in human liver cell culture. Tricresyl phosphate (TMPP), triphenyl phosphate (TPHP), tris(1,3-dichloropropyl) phosphate (TDCIPP), and 2-ethylhexyl diphenyl phosphate (EHDPP) induced the highest lipid accumulation by altering the expression of genes encoding hepatic de novo lipogenesis and mitochondrial dysfunction depicted by decreased cellular ATP production. Available in vitro data from ToxCast and in silico molecular docking suggests that pregnane X receptor (PXR) and peroxisome proliferator-activated receptor gamma (PPARγ) could be the molecular targets for the tested nFRs. The study identifies several nFRs, such as TMPP and EHDPP, TPHP, and TDCIPP, as potential risk factor for NAFLD and advances our understanding of the mechanisms involved, demonstrating the utility of an AOP-based strategy for screening and prioritizing chemicals and elucidating the molecular mechanisms of toxicity.
Keywords: Hepatocytes; simulace molekulového dockingu; Flame retardants; Adverse outcome pathways; Cell Culture Techniques; Pregnane X receptor; Adverse Outcome Pathways; dráhy škodlivých účinků; Metabolic disrupting chemicals; retardanty hoření; Molecular Docking Simulation; organofosfáty; hepatocyty; Humans; Flame Retardants; Organophosphates; buněčné kultury; lidé; Steatosis